THE EFFECT OF SERVICE QUALITY AND INSTITUTIONAL IMAGE ON STUDENT LOYALTY THROUGH SATISFACTION AS AN INTERVENING VARIABLE AT BATTUTA UNIVERSITY - Andrio Bukit; Endang Sulistya Rini; Syafrizal Helmi Situmorang (CV. RADJA PUBLIKA, 2025)
Universities play an important role as the main pillar in driving national transformation, both in terms of economy, social, and culture. In the era of globalization and revolution 4.0, the role of universities is becoming increasingly crucial in preparing the next generation to be competitive and innovative. The current phenomenon is that universities, especially private universities whose main source of funding comes from students, are experiencing problems with low levels of student loyalty. Several experts argue that student loyalty is greatly influenced by the level of student satisfaction which is factored by the quality of service and the image of the university itself. The purpose of this study is to determine and analyze the effect of service quality and institutional image on student loyalty at Battuta University through satisfaction. This type of research is associative research and the data used is quantitative data. The population of this study was all students of Battuta University, totaling 701 students. The technique for determining the number of samples used the Slovin formula so that a sample size of 258 students was obtained. The data analysis used is Partial Least Square Structural Equation Modeling. The results of the study directly show that service quality has a positive and significant effect on satisfaction, institutional image has a positive and significant effect on satisfaction, service quality has a positive and significant effect on student loyalty, institutional image has a positive and significant effect on student loyalty, and satisfaction has a positive and significant effect on student loyalty. Indirectly, service quality has a positive and significant effect on student loyalty through satisfaction, as well as institutional image has a positive and significant effect on student loyalty through satisfaction.